2019
DOI: 10.3390/app9040729
|View full text |Cite
|
Sign up to set email alerts
|

Yttria Ceria Co-Stabilized Zirconia Reinforced with Alumina and Strontium Hexaaluminate

Abstract: Zirconia materials are frequently used in dental applications due to their excellent strength and their tooth-like aspect. Standard yttria stabilized zirconia (Y-TZP) ceramics suffer, however, from moderate toughness and vulnerability to low-temperature degradation. In this study, 1Y6Ce-TZP materials reinforced with different amounts of alumina and/or strontium hexaaluminate were manufactured by slip casting and pressureless sintering at different temperatures to assess their mechanical properties, microstruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 39 publications
0
2
0
1
Order By: Relevance
“…They thought several different toughening mechanisms acting simultaneously in the material. Apart from the above ingredients of Santos et al’s study, Gommeringer et al (2019) reinforced 1Y6Ce-TZP materials with different amounts of alumina and/or strontium hexaalumina by slip casting and pressureless sintering at different temperatures. Then these materials underwent accession of their mechanical properties, microstructure, phase composition, and low-temperature degradation stability, which showed that they exhibited a high fracture resistance of 10–12 MPa m 1/2 .…”
Section: Adding Reinforcing Filler As Second Phase To Ceramic Matrixmentioning
confidence: 99%
“…They thought several different toughening mechanisms acting simultaneously in the material. Apart from the above ingredients of Santos et al’s study, Gommeringer et al (2019) reinforced 1Y6Ce-TZP materials with different amounts of alumina and/or strontium hexaalumina by slip casting and pressureless sintering at different temperatures. Then these materials underwent accession of their mechanical properties, microstructure, phase composition, and low-temperature degradation stability, which showed that they exhibited a high fracture resistance of 10–12 MPa m 1/2 .…”
Section: Adding Reinforcing Filler As Second Phase To Ceramic Matrixmentioning
confidence: 99%
“…O aditivo óxido de cério (IV) vem sendo estudado para redução das vacâncias de oxigênio pelo fato de ser tetravalente (Ce 4+ ) semelhante a zircônia e em quantidades apropriadas (cerca de 10-10,5% em mol) foi responsável pelo aumento da tenacidade à fratura para valores entre 10-12 MPa.m 1/2 , atuando na redução das vacâncias de oxigênio é possível reduzir o efeito da LTD (GOMMERINGER et al, 2019).…”
Section: Alternativas Da Literatura Científica Para Redução Do Efeito...unclassified
“…Additives used to stabilize zirconia not only produce crack-free zirconia, but also the sintered compact can retain the high temperature phase, i.e., the tetragonal phase at room temperature, where the equilibrium phase is monoclinic [1,2]. Among all zirconia ceramics, yttria tetragonal zirconia polycrystals (YTZPs) are the most attractive, for wide range of energy and biomedical applications, due to their unusual combination of excellent mechanical properties (i.e., high strength and high fracture toughness), as well as low thermal conductivity and biocompatibility [3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%